What Do Employers' Associations Do? - Pedro S. Martins (Institute of Labor Economics (IZA), 2020)
While trade unions have been studied in detail, there is virtually no economics research on employer associations (EAs), their counterparts in many countries. Here we argue that EAs are important economic agents as they provide sectoral public goods such as collective bargaining, training, and representation. However, their net contributions are complex because of a number of issues, including free riding, firm heterogeneity, and collusion. We then study EAs empirically by comparing sales, employment, productivity, and wages of affiliated and non-affiliated firms. Exploiting changes in firm affiliation status over time in Portugal, we find a positive but small affiliation premium along most dimensions. This premium follows an inverted-U-shaped relationship with EA coverage (defined as the percentage of workers in the relevant industry/region domain employed by affiliated firms). Sectors as a whole also appear to benefit from EA coverage, even if non-affiliated firms do worse.
Keywords: J58; L40; H41; K31; 330; employer organisations; firm performance; social dialogue; public goods